2010
DOI: 10.1038/oby.2009.332
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: In Bangladesh, overweight individuals have fewer symptoms of depression than nonoverweight individuals

Abstract: IntroductIonSeveral studies have found high rates of depression in populations of clinically overweight and obese people. This relationship has also been found in community studies where a high BMI and depression have been associated. The association between BMI and depressive symptoms has been so frequently reported in various samples that it has been suggested that there might be an intrinsic biological link that predisposes to both of these conditions (1). For instance, similar dysregulations of an array of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Shaheen Asghar et al . found that overweight individuals in Bangladesh had fewer symptoms of depression and concluded that obesity was an independent protective factor for depressive symptoms 38 . Another study from Hong Kong reported that obese elderly individuals were less likely to suffer from depressive symptoms than those of normal weight 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Shaheen Asghar et al . found that overweight individuals in Bangladesh had fewer symptoms of depression and concluded that obesity was an independent protective factor for depressive symptoms 38 . Another study from Hong Kong reported that obese elderly individuals were less likely to suffer from depressive symptoms than those of normal weight 39 .…”
Section: Discussionmentioning
confidence: 99%
“…The recognition of the worldwide problem of obesity by the WHO has put the issue fairly and squarely on all governments agenda as an item that needs special funding consideration and deliberation from many quarters, besides biophysical wellbeing. Perhaps people in environments which experience frequent famine may see it as a positive [27], whereas in most countries or places, many obese people are not happy with their lot and in consequence develop a range of psychological problems and defenses, that also compromise their health placing a further burden on themselves and the people who care for them, as well as most publicly subsidized medical systems [28].…”
Section: Discussionmentioning
confidence: 99%
“…19 In contrast, in cultures where obesity is not socially defamed this might not be the case. A study in Bangladesh by Asghar et al, 20 that reviewed more than a thousand individuals, showed reduced Montgomery-Åsberg Depression Rating Scale (MADRS) score in overweight and obese individuals (taking age and gender into consideration) (20). This supports the hypothesis that the lack of obesity stigma in some non-westernized societies may lead to better mental wellbeing among the obese and overweight individuals.…”
Section: Fat Mass Effectmentioning
confidence: 88%